2010
DOI: 10.1038/ni.1968
|View full text |Cite
|
Sign up to set email alerts
|

Lysine methylation of the NF-κB subunit RelA by SETD6 couples activity of the histone methyltransferase GLP at chromatin to tonic repression of NF-κB signaling

Abstract: Protein lysine methylation signaling is implicated in diverse biological and disease processes. Yet the catalytic activity and substrate specificity are unknown for many human protein lysine methyltransferases (PKMTs). We screened over forty candidate PKMTs and identified SETD6 as a methyltransferase that monomethylates chromatin-associated NF-κB RelA at lysine 310 (RelAK310me1). SETD6-mediated methylation rendered RelA inert and attenuated RelA-driven transcriptional programs, including inflammatory responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
291
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(301 citation statements)
references
References 48 publications
10
291
0
Order By: Relevance
“…It is well established that the NF-B pathway is regulated exceptionally tightly by several post-translational modifications, including phosphorylation, ubiquitination, acetylation, and methylation (11)(12)(13). However, it remains to be determined whether these modifications influence muscle function, size, or atrophy.…”
mentioning
confidence: 99%
“…It is well established that the NF-B pathway is regulated exceptionally tightly by several post-translational modifications, including phosphorylation, ubiquitination, acetylation, and methylation (11)(12)(13). However, it remains to be determined whether these modifications influence muscle function, size, or atrophy.…”
mentioning
confidence: 99%
“…Methylation of RelA by SETD6 inhibits the transactivation activity of RelA (25). We detected RelA bound to the promoter of GnRH via ChIP in GT1-7 cells transfected with SETD6…”
Section: Significancementioning
confidence: 99%
“…4B). Ala360Glu is located in one of the α-helices of the C-terminal domain of the SETD6 protein (25,28), and the Glu residue is highly conserved from chickens to humans (Fig. 4C).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Recent work of several laboratories has identified methylation as another regulatory RelA modification that controls gene expression downstream of TNFα and IL-1β signaling. Several histone lysine methyltransferases, including SET7/9, SETD6, and NSD1, have been shown to both positively and negatively regulate NF-κB through direct monomethylation or dimethylation of distinct lysine residues in RelA (12)(13)(14)(15). Recent studies also have shown that RelA is methylated by the type II protein arginine methyltransferase 5 (PRMT5), which catalyzes the synthesis of ω-N Gmonomethylarginine (MMA) and symmetric ω-N G ,N′ G -dimethylarginine (SDMA) (16,17).…”
mentioning
confidence: 99%